A brief review of interplay between vitamin D and angiotensin‐converting enzyme 2: Implications for a potential treatment for COVID‐19. (25th June 2020) - Malek Mahdavi, Aida
Summary: The novel coronavirus disease 2019 (COVID‐19) is rapidly expanding and causing many deaths all over the world with the World Health Organization (WHO) declaring a pandemic in March 2020. Current therapeutic options are limited and there is no registered and/or definite treatment or vaccine for this disease or the causative infection, severe acute respiratory coronavirus 2 syndrome (SARS‐CoV‐2). Angiotensin‐converting enzyme 2 (ACE2), a part of the renin‐angiotensin system (RAS), serves as the major entry point into cells for SARS‐CoV‐2 which attaches to human ACE2, thereby reducing the expression of ACE2 and causing lung injury and pneumonia. Vitamin D, a fat‐soluble‐vitamin, is a negative endocrine RAS modulator and inhibits renin expression and generation. It can induce ACE2/Ang‐(1‐7)/MasR axis activity and inhibits renin and the ACE/Ang II/AT1R axis, thereby increasing expression and concentration of ACE2, MasR and Ang‐(1‐7) and having a potential protective role against acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Therefore, targeting the unbalanced RAS and ACE2 down‐regulation with vitamin D in SARS‐CoV‐2 infection is a potential therapeutic approach to combat COVID‐19 and induced ARDS.